Distributed Arduino for Communication Agriculture - Fredy Susanto; Ari Asmawati; Erna Astriyani (CCIT (Creative Communication and Innovative Technology) Journal, 2021)
The needs of human life today, are felt to require the help of technology. Utilization of information technology has reached the countryside and all regions, beaches, mountains and cities. Information on agricultural or plantation products is very important for rural and urban communities, where yields and their development are indicators of decision-making and policy. Currently this information is very difficult to obtain, let alone collided with the complexity of problems in life. The method used is a distributed system method where the information produced by farmers regarding their harvest is distributed host to host (distributed system) via Arduino Uno. The use of Arduino Uno devices means the use of minimalist devices or embedded systems to minimize resources, and save energy